2016
DOI: 10.1097/inf.0000000000001017
|View full text |Cite
|
Sign up to set email alerts
|

Post-bronchiolitis Use of Asthma Medication

Abstract: Children hospitalized for rhinovirus-positive bronchiolitis used long-term asthma controller medication more often than those hospitalized for rhinovirus-negative bronchiolitis during first year after hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…However, our results were confirmed when examining ICS or montelukast use by age 3 years, a more objective outcome, and development of doctor-diagnosed asthma by age 3 years. 13 Second, the severe bronchiolitis profiles identified in the current study have been defined in a cohort of hospitalized infants, which only represent a small proportion of all patients with bronchiolitis. It is likely that additional bronchiolitis profiles exist, including milder cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results were confirmed when examining ICS or montelukast use by age 3 years, a more objective outcome, and development of doctor-diagnosed asthma by age 3 years. 13 Second, the severe bronchiolitis profiles identified in the current study have been defined in a cohort of hospitalized infants, which only represent a small proportion of all patients with bronchiolitis. It is likely that additional bronchiolitis profiles exist, including milder cases.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 Respiratory tract infections with respiratory syncytial virus (RSV) and rhinovirus, the most commonly identified pathogens in patients with bronchiolitis, have both been associated with later development of recurrent wheezing and asthma, although stronger associations have been reported for those with rhinovirus. 1,2,7,8,12,13 Moreover, among patients with bronchiolitis or early-life wheezing illnesses, rhinovirus infection is most often seen in children with clinical histories suggesting susceptibility to asthma (eg, history of wheezing and sensitization). 14,15 Using a statistical clustering approach in multicenter cohorts of US and Finnish children hospitalized with bronchiolitis, we recently identified distinct severe bronchiolitis profiles.…”
mentioning
confidence: 99%
“…In a recently published study, children with RV positive bronchiolitis used 4.1-fold more asthma controller medication than children with RSV positive bronchiolitis during 12-month follow-up (45). Our results add that RVA- and RVC-associated first wheezing episodes are of particular risk for the initiation of regular controller medication for asthma symptoms when compared to non-RV associated wheezing.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have shown that the key enzymes in the de novo lipogenesis, including fatty acid synthase (FASN), acetyl-CoA carboxylase (ACC), ATP-citrate lyase (ACLY) (Figure 1), were abnormally upregulated in CSCs, leading to the upregulation of de novo lipogenesis (Gopal et al, 1963;Santos and Schulze, 2012;Ameer et al, 2014;Bergroth et al, 2016). For example, in breast cancer cells, the enhanced expression of ACLY was related to the upregulation of snail proteins, which triggered tumorigenesis and enhanced cancer stemness (Hanai et al, 2013).…”
Section: Lipid Synthesismentioning
confidence: 99%